Effects of texture and twinning on the torsional behavior of magnesium alloy solid rod: A crystal plasticity approach in comparison with uniaxial tension/compression. (1st February 2021) - Zhang, Xiaodan; Li, Shangming; Guo, Xiaoqian; Wang, Huamiao; Yu, Qin; Wu, Peidong
Highlights: Effects of texture and twinning on the tensile, compressive, and torsional behaviors of mg alloy solid rod are systematically investigated through crystal plasticity model. Torsional behavior and the resultant swift effect depend strongly on the texture and twinning. The inhomogeneous nature of torsional deformation results in unique distributions of internal stress and twin volume fraction within mg alloy solid rod. The different behaviors of the mg alloys associated with different textures and loadings result from the different operating deformation mechanisms. Abstract: The elastic visco-plastic self-consistent model with the twinning and detwinning scheme, in conjunction with a torsion specific finite element approach, is employed to model the deformation behavior of magnesium alloy AZ31 solid rod with different initial textures, including ideal basal, rolled, extruded, and random. Besides the loading with nearly homogenous deformation (tension and compression), loading paths with inhomogeneous deformation are investigated particularly under free-end and fixed-end torsions. Simulation reveals that the deformation mechanisms alter significantly with varying the different initial textures and different loading paths, leading to variances in stress-strain response, Swift effect, and deformation texture. In particular, our crystal plasticity model well captures the inhomogeneous distributions of internal stress and twin volume fraction within the solid rod under torsion. This is particularly significant as our torsion-specific crystal plasticity model provides a numerical tool that can be used to tune gradient twin structures via torsion of solid rod to improve the mechanical properties of magnesium alloy. Graphic abstract: Image, graphical abstract